Anne of Austria’s autographs in Russian collections - V. V. Shishkin (Шаги)
The article precedes the publication of three documents signed and personally written by Queen of France Anne of Austria (1601–1666), wife of Louis XIII and mother of Louis XIV. They are stored in the Scientific and Historical Archive of the Saint Petersburg Institute of History of the Russian Academy of Sciences (as part of the collection of Nikolay Likhachev), and in the Department of Written Sources of the State Historical Museum in Moscow. The publication complements the previous publication of seven letters by the Queen from the collections of Peter Dubrovsky, Peter Sukhtelen and the Hermitage collection, which appeared in 1997 in the yearbook “Middle Ages.” It includes an order of Anna of Austria regarding the protection of the city gates of Paris in September 1636 during the Franco-Spanish confrontation within the framework of the Thirty Years War, as well as her official message to Marshal de Lambert, governor of the border fortress of Metz, demanding the maintenance of military and administrative order in connection with the death of Louis XIII and the accession of the child king. The third of the messages, written in her own hand and of a private nature, is a request to the Grand Duke of Tuscany to influence one of his Florentine subjects, Luca Fabroni, to sell Anne of Austria the jewelry of Maria de Medici that ended up in his hands. All three autographs are of historical value and serve as an important illustration of socio-political events in France in the first half of the 17th century.